1998
DOI: 10.1089/cbr.1998.13.177
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Tumor Folate Receptors using 111IN-DTPA-Methotrexate

Abstract: It is known that membrane folic acid receptors are responsible for cellular accumulation of folate and folate analogs, such as methotrexate, and overexpressed on various tumor cells. This study was aimed to develop an 111In labelled DTPA-methotrexate (DTPA-MTX) to image tumor folate receptors in vivo. DTPA-MTX was synthesized by reacting ethylenediamine with MTX. The resulting amino analogue of MTX was reacted with DTPA dianhydride in basic aqueous solution followed by dialysis. Tissue distribution was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…SPECT (single photon-emission computerized tomography) images obtained with this substance demonstrated that the complex accumulated in the kidney and liver as well as in malignant, but not benign ovarian cancers [37,39]. These studies have been extended by Leamon and Low amongst others [39] to the production of 99m Tc-folate conjugates with the hope of reducing the cost and half-life of the imaging agent with substantially reduced exposure of vital organs to the nuclide [40][41][42][43]. Furthermore, the 140 keV c-radiation emitted by 99m Tc is optimal for standard imaging equipment.…”
Section: Radiodiagnostic Imaging With Folate Analoguesmentioning
confidence: 99%
“…SPECT (single photon-emission computerized tomography) images obtained with this substance demonstrated that the complex accumulated in the kidney and liver as well as in malignant, but not benign ovarian cancers [37,39]. These studies have been extended by Leamon and Low amongst others [39] to the production of 99m Tc-folate conjugates with the hope of reducing the cost and half-life of the imaging agent with substantially reduced exposure of vital organs to the nuclide [40][41][42][43]. Furthermore, the 140 keV c-radiation emitted by 99m Tc is optimal for standard imaging equipment.…”
Section: Radiodiagnostic Imaging With Folate Analoguesmentioning
confidence: 99%
“…9 Molecular targets (e.g., estrogen, progestin, folate, retinoic acid receptors, BRCA-1, HER-2/neu, p53, cyclin D1) provide more accurate functional information for breast cancer diagnosis and treatment. [10][11][12][13][14][15][16][17] Tagging molecular targets with radionuclides can increase our understanding of pharmacokinetic, pharmacodynamic and metabolic imaging patterns of the agent, thereby providing information useful for characterizing tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Above reports provided limited uptake of MTX radioagents by FR-positive cancer cell lines especially in comparison to folate-based radioagents. However, results of in vivo or ex vivo biodistribution showed detectable MTX radioagents uptake at tumor sites, but also substantial uptake in spleen.…”
Section: Radionuclide-labeled Mtx Agentsmentioning
confidence: 99%
“…113,114 Other investigated radioligands based on MTX vector also showed unsatisfactory traceability of FR-expressing tumors in rodent models. γ-Emitting [ 111 In]In-DTPA-ethylenediamine-MTX 115 showed very low uptake in breast tumor, but still superior than [ 111 In]In-DTPA complex and sensitive to FA blockage. [ 68 Ga]Ga-or [ 99m Tc]Tc-chitosan-polyglutamate-MTX complexes, 116 both obtained in direct labeling, showed negligible human breast tumor targetability (tumor-to-blood ratios below 1) throughout in vivo biodistribution.…”
Section: Radionuclide-labeled Mtx Agentsmentioning
confidence: 99%